Gender Equality on Nahdlatul Ulama and Muhammadiyah Perspective - Abidin, Ahmad Zainal; Ratnawati, Dewi; Taufiqurrahim, Taufiqurrohim; Aziz, Thoriqul (PALASTREN: Jurnal Studi Gender, 2020)
Factors related to the discrimination of women's rights include religious perspectives that are contaminated by cultural patriarchy, race, social strata, gender identity, sexual orientation, age, and health. Liberation of women's rights can be realized by Islamic organizations which are free from the negative influence of patriarchal culture. These organizations are Nahdatul Ulama 'and Muhammadiyah. The focus of the discussion includes the gender perspective of Nahdatul Ulama and Muhammadiyah. it also want to trace the gender equality perspective of Nahdatul Ulama' and Muhammadiyah. The method used by the writer is in the form of library research. Sources of data are taken from relevant theme raised by the author. The results of research are giving freedom for women to realize their rights and potential both in the public sector and domestic sector.